2022
DOI: 10.3389/fphys.2022.976421
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium candidum polysaccharide reduce atopic dermatitis symptoms and modulate gut microbiota in DNFB-induced AD-like mice

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease with a high prevalence worldwide. Increasing evidence suggests that the gut microbiota plays an important role in the pathogenesis of AD. In this study, we sought to verify the effect of Dendrobium candidum polysaccharides (DCP) on AD induced by 2,4-Dinitrofluorobenzene (DNFB) in Balb/c mice regarding its impact on the intestinal microbiome. We found that 2-week oral administration of DCP improved AD-like symptoms and histological damage of skin, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Tregs can prevent the polarisation of Th2 cells by secreting inhibitory cytokines including IL-10, IL-35, and TNF-β, while AD is generally considered a Th2-driven disease [149] Natural polysaccharides have a function of immunostimulating effects and can increase the proportion of Tregs [150]. Polysaccharides from Angelica gigas Nakai (ISAg) induced the polarization of CD4 + T cells toward the acquisition of the Th1 phenotype and the expansion of Treg in Yet40 B6 mice, which suggests that ISAg may be effective for AD therapy [88]. Fucus vesiculosus polysaccharides have demonstrated immune-stimulating effects, leading to an increase in Tregs [100].…”
Section: Restoring Treg Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tregs can prevent the polarisation of Th2 cells by secreting inhibitory cytokines including IL-10, IL-35, and TNF-β, while AD is generally considered a Th2-driven disease [149] Natural polysaccharides have a function of immunostimulating effects and can increase the proportion of Tregs [150]. Polysaccharides from Angelica gigas Nakai (ISAg) induced the polarization of CD4 + T cells toward the acquisition of the Th1 phenotype and the expansion of Treg in Yet40 B6 mice, which suggests that ISAg may be effective for AD therapy [88]. Fucus vesiculosus polysaccharides have demonstrated immune-stimulating effects, leading to an increase in Tregs [100].…”
Section: Restoring Treg Cell Functionmentioning
confidence: 99%
“…Inhibition of pathogenic colonization of S. aureus is an important approach for polysaccharides in regulating the skin microbiome in the context of AD. Xyloglucan-containing products have been shown to inhibit the colonization of S. aureus and reduce its adhesion and penetration on the skin of infected mice [88].…”
Section: Regulating Microbiome 441 Skin Microbiomementioning
confidence: 99%
“…A total of 18 female BALB/c mice (6-week-old) were purchased from SLACOM, and AD was induced by 2,4-dinitrofluorobenzene (DNFB) treatment as previously described. 21 Briefly, 1% DNFB (Macklin) was dissolved in an acetone/olive oil (1:3) solution. Mice were randomized into three groups (n = 6/group): control, AD, and AD + miR-193b groups.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…158 In a study on herbal monomers, the oral Dendrobium candidum polysaccharides ( DCP ) treatment restores the relative abundance of Desulfovibrio and Blautia in DNFB-induced AD-like mice, down to near that of healthy mice. 157 Regarding the herbal compound, Huang-Lian-Jie-Du Decoction and the water-soluble-fraction could markedly alleviate AD-like symptoms induced by DNCB and MC903 in mice, possibly improving the epidermal barrier function and inhibiting skin inflammation via suppressing the activation of NF-κB and MAPKs pathways and regulation of the gut microbiota dysbiosis. 164 Chun et al demonstrated that Sihocheonggan-Tang (SHCGT) ameliorates DNCB-induced AD symptoms in mice by modulating the immune response and altering the gut microbiome composition.…”
Section: Natural Products For the Treatment Of Admentioning
confidence: 99%